Role of Fms‐like Tyrosine Kinase 3 Ligand as a Potential Biologic Marker of Lymphoma in Primary Sjögren's Syndrome. Issue 12 (27th November 2013) - Tobón, Gabriel J.; Saraux, Alain; Gottenberg, Jacques‐Eric; Quartuccio, Luca; Fabris, Martina; Seror, Raphaèle; Devauchelle‐Pensec, Valérie; Morel, Jacques; Rist, Stéphanie; Mariette, Xavier; De Vita, Salvatore; Youinou, Pierre; et al.
Abstract : Objective: Patients with primary Sjögren's syndrome (SS) are at greater risk of developing lymphoma. This study was undertaken to evaluate whether the Fms‐like tyrosine kinase 3 ligand (Flt‐3L) might be associated with lymphoma in primary SS. Methods: Serum levels of Flt‐3L were measured in 369 patients with primary SS from the French Assessment of Systemic Signs and Evolution of Sjögren's Syndrome study cohort and in 10 patients with primary SS at the time of lymphoma diagnosis in an Italian cohort. Associations between increased levels of Flt‐3L and a history of lymphoma, history of previously diagnosed criteria related to a high risk of lymphoma, and greater extent of disease activity were evaluated. Results: Among patients with primary SS, higher levels of Flt‐3L were significantly associated with a history of lymphoma ( P = 0.0001). Previous markers for risk of lymphoma development, such as presence of purpura, low levels of C4, presence of lymphocytopenia, low levels of IgM, high levels of β2 ‐microglobulin, and a higher primary SS disease activity score, were all associated with higher levels of Flt‐3L. The levels of Flt‐3L were also increased in serum obtained from patients with primary SS at the time of lymphoma diagnosis. Furthermore, the Flt‐3L levels were elevated in the serum of 6 patients up to 94 months (mean 46 months) prior to the diagnosis of lymphoma. Receiver operating characteristic curve analysis showed that an Flt‐3L level of 175 pg/ml was the ideal cutoff value for demonstrating an association with lymphoma (specificity 97.5%, sensitivity 44%, negative predictive value 97%). Conclusion: Flt‐3L is associated with lymphoma in primary SS, and constitutes a good biologic marker. Higher levels of this cytokine are present several years before the diagnosis of lymphoma, and may be useful as a predictive marker of lymphoproliferative disorders in primary SS.